Stromal markers of activated tumor associated fibroblasts predict poor survival and are associated with necrosis in non-small cell lung cancer. (September 2019) - Alcaraz, Jordi; Carrasco, Josep Lluís; Millares, Laura; Luis, Iuliana-Cristiana; Fernández-Porras, Francisco J.; Martínez-Romero, Anabel; Diaz-Valdivia, Natalia; De Cos, Julio Sánchez; Rami-Porta, Ramon; Seijo, Luis; Ramírez, Josep; Pajares, María José; et al.
Highlights: The prognostic value of fibrotic markers α-SMA and fibrillar collagens is unclear in NSCLC. Fibrotic markers α-SMA and fibrillar collagens were associated with poor survival. Prognostic value of α-SMA and fibrillar collagens was independent of TNM staging. Fibrotic markers were associated with necrosis, which is often indicative of hypoxia. Patients with desmoplastic tumors are at higher risk, and could be considered for adjuvant therapy. Abstract: Objectives: Tumor associated fibroblasts (TAFs) are essential contributors of the progression of non-small cell lung cancer (NSCLC). Most lung TAFs exhibit an activated phenotype characterized by the expression of α-SMA and fibrillar collagens. However, the prognostic value of these activation markers in NSCLC remains unclear. Material and Methods: We conducted a quantitative image analysis of α-SMA immunostaining and picrosirius red staining of fibrillar collagens imaged by bright-field and polarized microscopy, respectively, using tissue microarrays with samples from 220 surgical patients, which elicited a percentage of positive staining area for each marker and patient. Results: Kaplan-Meier curves showed that all TAF activation markers were significantly associated with poor survival, and their prognostic value was independent of TNM staging as revealed by multivariate analysis, which elicited an adjusted increased risk of death after 3 years of 129% and 94% for fibrillar collagens imaged with bright-field (p = 0.004) and polarized light (p = 0.003), respectively, and of 89% for α-SMA (p = 0.009). We also found a significant association between all TAF activation markers and tumor necrosis, which is often indicative of hypoxia, supporting a pathologic link between tumor desmoplasia and necrosis/hypoxia. Conclusions: Our findings identify patients with large histologic coverage of fibrillar collagens and α-SMA + TAFs to be at higher risk of recurrence and death, supporting that they could be considered for adjuvant therapy.